Foundation design : principles and practices - Coduto, Donald P. (Upper Saddle River, N.J. : Prentice Hall, 2001)
"Using a design-oriented approach that addresses geotechnical, structural, and construction aspects of foundation engineering, this book explores practical methods of designing structural foundations, while emphasizing and explaining how and why foundations behave the way they do. It explains the theories and experimental data behind the design procedures, and how to apply this information to real-world problems. Covers general principles (performance requirements, soil mechanics, site exploration and characterization); shallow foundations (bearing capacity, settlement, spread footings
Foundations in Civil Engineering -- The Emergence of Modern Foundation Engineering -- The Foundation Engineer -- Uncertainties -- Building Codes -- Classification of Foundations -- Performance Requirements -- Design Loads -- Strength Requirements -- Serviceability Requirements -- Constructibility Requirements -- Economic Requirements -- Soil Mechanics -- Soil Composition -- Soil Classification -- Groundwater -- Stress -- Compressibility and Settlement -- Strength -- Site Exploration and Characterization -- Site Exploration -- Laboratory Testing -- In-Situ Testing -- Synthesis of Field and Laboratory Data -- Economics -- Shallow Foundation Analysis and Design -- Shallow Foundations -- Spread Footings -- Mats -- Bearing Pressure -- Shallow Foundations--Bearing Capacity -- Bearing Capacity Failures -- Bearing Capacity Analyses in Soil--General Shear Case -- Groundwater Effects -- Allowable Bearing Capacity -- Selection of Soil Strength Parameters -- Bearing Capacity Analyses--Local and Punching Shear Cases -- Bearing Capacity on Layered Soils -- Accuracy of Bearing Capacity Analyses -- Bearing Spreadsheet -- Shallow Foundations--Settlement -- Design Requirements -- Overview of Settlement Analysis Methods -- Induced Stresses Beneath Shallow Foundations -- Settlement Analyses Based on Laboratory Tests -- Settlement Spreadsheet -- Settlement Analyses Based on In-Situ Tests -- Schmertmann Spreadsheet -- Settlement of Foundations of Stratified Soils -- Differential Settlement -- Rate of Settlement.
Includes bibliographical references (pages 849-874) and index.
Keywords: Foundations